RELEVANCE ECONOMIC CONSIDERATIONS FOR OMITTING COPYRIGHT INFRINGEMENT IN INDONESIA - Kastowo, Chryssantus; Christianib, Theresia Anita; Retnowati, Anny (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is committed to protecting copyright. Indonesia participates in various international conventions in the field of intellectual property and amends copyright laws. Indonesia changed the nature of the ordinary offense to complaint offense as a form of recognition that copyright is a personal right. This change in the offense should change the paradigm of copyright as private property. This article will discuss how this paradigm shift in copyright has implications for the enforcement of copyright law in Indonesia. This article base on normative legal research focusing on secondary data. The analysis in this study uses a conceptual approach. The results showed that copyright regulation as individual rights. The right owner is personally responsible for the copyrights he owns. Until now, copyright violations are still widespread in society. Copyright infringement does not always have the economic motivation, so it does not always result in losses for the creator—the results in violations of rights, which does not always lead to disputes. The absence of a dispute does not mean there is no copyright infringement. Based on economic considerations, the creator allowed the budgeting to occur, and without a law enforcement process. Copyright rules as an expression of appreciation from the state for creative subjects are meaningless if there is the elimination of violations. The creator should support all efforts to protect copyright, mainly if copyright infringement occurs.